Hippocampal and Retrosplenial Goal Distance Coding After Long-term Consolidation of a Real-World Environment. (20th February 2019) - Patai, E Zita; Javadi, Amir-Homayoun; Ozubko, Jason D; O'Callaghan, Andrew; Ji, Shuman; Robin, Jessica; Grady, Cheryl; Winocur, Gordon; Rosenbaum, R Shayna; Moscovitch, Morris; Spiers, Hugo J
Abstract: Recent research indicates the hippocampus may code the distance to the goal during navigation of newly learned environments. It is unclear however, whether this also pertains to highly familiar environments where extensive systems-level consolidation is thought to have transformed mnemonic representations. Here we recorded fMRI while University College London and Imperial College London students navigated virtual simulations of their own familiar campus (>2 years of exposure) and the other campus learned days before scanning. Posterior hippocampal activity tracked the distance to the goal in the newly learned campus, as well as in familiar environments when the future route contained many turns. By contrast retrosplenial cortex only tracked the distance to the goal in the familiar campus. All of these responses were abolished when participants were guided to their goal by external cues. These results open new avenues of research on navigation and consolidation of spatial information and underscore the notion that the hippocampus continues to play a role in navigation when detailed processing of the environment is needed for navigation.